Invertebrates of Siberia, a Potential Source of Animal Protein for Innovative Food and Feed Production: Biomass Nutrient Composition Change in the Earthworm Eisenia fetida (Savigny, 1826) and the House Cricket Acheta domesticus (Linnaeus, 1758) - Sergei E. Tshernyshev; Andrei S. Babenko; Irina B. Babkina; Ruslan T.-O. Baghirov; Vera P. Modyaeva; Margarita D. Morozova; Ksenia E. Skribtcova; Elena Y. Subbotina; Mikhail V. Shcherbakov; Anastasia V. Simakova (Insects, 2025)
The possibility of designing the nutrient composition of invertebrate biomass was investigated. Two model species of terrestrial invertebrates, the house cricket Acheta domesticus (Linnaeus, 1758) and the earthworm Eisenia fetida (Savigny, 1826), were studied after feeding on substrates alternately enriched with certain nutrient precursors proposed in single and double doses. Crickets and earthworms showed similar tendencies to increase the B vitamin content of those vitamins whose initial level was high. Double-dose enrichment of the food substrate increased the levels of vitamin C, fat-soluble vitamins and most B vitamins. In a control group of crickets, vitamin C levels were 1.5 times lower than in a control group of earthworms. After enrichment of the feed substrate, the vitamin C content in the biomass of the crickets did not change significantly, but in the earthworms it increased significantly. The content of a wide range of minerals did not change after single-dose enrichment, but some micro-elements such as Pb and Se decreased significantly in earthworms after double-dose enrichment of the feed substrate. The calorific value of crickets was twice that of earthworms and did not change significantly after double-dose enrichment. It is shown that the nutrient composition of invertebrate biomass can be increased by enriching the feed substrate with precursors. The most effective increases are observed for all vitamins and several minerals. The results can be used to achieve specific nutrient concentrations in biomass for food and medical purposes.